Dynamic capabilities in manufacturing - Sarjana, Sri (Journal of Entrepreneurship, Business and Economics, 2015)
The aim of this study is to identify and analyze of influence manufacturing capability and knowledge resources on dynamic capability also implication toward enterprise performance. Environmental tur-bulences are existed as intervening variable enterprise performance. This finding integrates insights in dynamic capability framework into a generalization of the enterprise performance in manufacturing. This research applied a random sampling method to collect responses and increase the generalizability obtained number of respondents. Hence, this study applies questionnaire methods as the main research tools in order to conduct an in-depth investigation. The research used mix method in triangulation transformation model. Furthermore, this research is expected to provide enterprises with valua-ble suggestions for management practices to increase enterprise performance in manufactures. Research paper Reference to this paper should be made as follows: Sarjana, S. (2015). “Dynamic capabilities in manufacturing: The main role of manufacturing capability, knowledge resources and environmental turbulence to improve enterprise”, Journal of Entrepreneurship, Business and Economics, Vol. 3, No. 2, pp. 41–64